PERUBAHAN SPASIAL DAN SOSIAL-BUDAYA SEBAGAI DAMPAK MEGAURBAN DI DAERAH PINGGIRAN KOTA SEMARANG - Prihanto, Teguh (Semarang State University, 2010)
Abstract:Â Â Â TheÂ researchÂ ofÂ spatialÂ andÂ socio-culturalÂ changesÂ as megaurbanÂ impactsÂ inÂ urban fringeÂ areaÂ ofÂ SemarangÂ hasÂ severalÂ aims:Â (1)Â toÂ discoverÂ andÂ examineÂ whatÂ factorsÂ cause megaurban process,Â (2)Â toÂ find a mechanism or process megaurban place, andÂ (3)Â toÂ studyÂ the effects of the process (especially spatial, socio-cultural, economics and demography. TheÂ locationÂ ofÂ thisÂ studyÂ isÂ theÂ outskirtsÂ ofÂ Semarang.Â TheÂ cityÂ wasÂ chosenÂ becauseÂ itÂ hasÂ a strategicÂ role.Â ThisÂ researchÂ willÂ beÂ approachedÂ inÂ anÂ integratedÂ paradigmÂ isÂ naturalisticÂ or phenomenology.Â ThisÂ approachÂ doesÂ notÂ meanÂ denyingÂ theÂ positivisticÂ paradigm,Â butÂ instead attemptÂ toÂ